TEACHING ENGLISH BY USING VLOGGER VIDEO TO INCREASE VOCABULARY - hafidah fitri; Hasanul Misbah (Universitas Galuh, 2021)
The research aimed to analyze Vocabulary by using Vlogger Video through visual material, vlogger video. The research was conduct in the class 8.7 of SMPN 03 Tang-Sel. Researcher choose one classes as Experimental class. The used purposive sampling technique by choosing 30 studentsand conducted pre-test and post-test to gather the researcher data. The experimental class was using Vlogger Video on learning English. The research lasted for one month and researcher compared the results of pre-test and post-test through SPSS 22 to conclude the results of research. The experimental class results would be the conclusion of research as this class used Vlogger Video during the lesson. the value of the df t-value is searched based on n=29 with a range of 0,025. Its df t-value is 2,045. Because the t-test value is higher than the df t-value (5000>2045) h1 is accepted and h0 is rejected, so the learning method is successful in increasing students’ vocabulary skill. It means that teaching english by using vlogger video to increase vocabulary was significant.